ANALISIS PELAKSANAAN REFORMA AGRARIA DI KECAMATAN BAGELEN KABUPATEN PURWOREJO PROVINSI JAWA TENGAH - , Atop Widodo, S.SiT ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Implementation of Agrarian Reform in Bagelen Sub District is intended as an effort to address poverty alleviation, environmental conservation and improving the quality of land services. The expected benefits from the implementation of agrarian reform, among others, strengthening the asset (asset reform) is by the issuance of certificates of land and provision of access (access reform) in the form of rubber and rubber planting training. Implementation of Agrarian Reform in Bagelen Sub District especially in the Somorejo and Hargorojo Village still leave many issues including the strengthening of asset that can not be done fully and land prepared for the provision of access in the form of critical land that is prone to landslides and drought. This research was conducted to analyze the mechanism and delivery system and the role of agrarian reform agency in addressing problems in strengthening the asset and granting access in Bagelen Sub District. The method used in this research is descriptive method and data used consists of primary data and secondary data. Primary data were collected through interviews with relevant agencies and a questionnaire addressed to the farmers who joined in the Agrarian Reform Communities Movement Sido Dadi Mulyo Bagelen Sub District, while the secondary data were obtained from various sources. Furthermore, primary and secondary data were simplified and processed with the help of Microsoft Exell software so it can be analyzed and presented in the form of text and numbers that may reflect the fact the implementation of agrarian reform in the Somorejo and Hargorojo Village. Further, the results of analysis were compared with the manual execution of Agrarian Reform made by the National Land Agency Republic of Indonesia. Therefore, a series of mechanisms and compliance delivery system and the role of agencies in addressing problems in strengthening the asset and granting access in the Somorejo and Hargorojo Village can be examinated. The results showed that the mechanism and the most appropriate delivery system is applied in the implementation of agrarian reform in the Somorejo and Hargorojo Village is the Model III, but until the end of 2009 only has 11 fields (6.18%) of 178 parcels of land that has been object of Agrarian Reform for a strengthening asset. This problem is caused by ineffective use of PRONA budget and support Purworejo District Government. Meanwhile, given the access reform has not created a series of mechanisms are intact and integrated production due to less optimal role of agencies in utilizing the commitment of the National Land Agency Regional Office of Central Java Province and Purworejo District Land Office and the support of County Government Purworejo and PT. Perkebunan Nusantara IX.